Induction of apoptosis by Drosophila reaper, hid and grim through inhibition of IAP function - Goyal, Lakshmi (Oxford University Press, 2000)
Induction of apoptosis in Drosophila requires the activity of three closely linked genes, reaper, hid and grim. Here we show that the proteins encoded by reaper, hid and grim activate cell death by inhibiting the anti-apoptotic activity of the Drosophila IAP1 (diap1) protein. In a genetic modifier screen, both loss-of-function and gain-of-function alleles in the endogenous diap1 gene were obtained, and the mutant proteins were functionally and biochemically characterized. Gain-of-function mutations in diap1 strongly suppressed reaper-, hid- and grim-induced apoptosis. Sequence analysis of these alleles revealed that they were caused by single amino acid changes in the baculovirus IAP repeat domains of diap1, a domain implicated in binding REAPER, HID and GRIM. Significantly, the corresponding mutant DIAP1 proteins displayed greatly reduced binding of REAPER, HID and GRIM, indicating that REAPER, HID and GRIM kill by forming a complex with DIAP1. These data provide strong in vivo evidence for a previously published model of cell death regulation in Drosophila.